2021
DOI: 10.1038/s41598-021-92502-7
|View full text |Cite
|
Sign up to set email alerts
|

Inconsistent response of bacterial phyla diversity and abundance to soil salinity in a Chinese delta

Abstract: Soil salinization is an increasingly serious problem and decreases crop yields in the Yellow River Delta (YRD), but its effects on bacterial community and diversity at the phylum level are not well known. We used high-throughput sequencing of soil bacterial 16S rRNA to identify soil bacterial communities and diversity across a gradient of soil salinity (electrical conductivity), namely, S1: low salinity level (1.78 ds/m), S2: medium salinity level (3.16 ds/m), S3: high salinity level (17.26 ds/m), S4: extreme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 32 publications
(54 reference statements)
3
9
2
Order By: Relevance
“…However, biochar amendment increased the bacterial richness and diversity under salinity stress. The results of our study are in accordance with the findings of Yang et al (2021), who reported that extreme salinity (34.41 dS m −1 ) lowered significantly Shannon, Ace, and Chao 1. However, Han et al (2017) investigated that biochar application had shown a positive effect on the bacterial structure under saline conditions.…”
Section: Effect Of Biochar On Bacterial Diversity and Richness Indexsupporting
confidence: 93%
See 3 more Smart Citations
“…However, biochar amendment increased the bacterial richness and diversity under salinity stress. The results of our study are in accordance with the findings of Yang et al (2021), who reported that extreme salinity (34.41 dS m −1 ) lowered significantly Shannon, Ace, and Chao 1. However, Han et al (2017) investigated that biochar application had shown a positive effect on the bacterial structure under saline conditions.…”
Section: Effect Of Biochar On Bacterial Diversity and Richness Indexsupporting
confidence: 93%
“…Zhang et al (2021) has reported that increasing some phylum (Bacteroidetes, Gemmatimondetes, and Firmicutes) and bacterial communities showed tolerance and strongly structured with increasing salinity stress. In contrast, Yang et al (2021) revealed that extreme salinity levels (34.41 dS m −1 ) significantly decreased the abundance of Proteobacteria, Actinobacteria, and Acidobacteria. The pH has a great impact on the relative abundance of bacteria on phylum and genus levels (Wang et al, 2019).…”
Section: Effect Of Biochar On Microbial Community On Phylum and Genus Levelsmentioning
confidence: 73%
See 2 more Smart Citations
“…Existing studies on microbial community diversity in saline-alkaline land focused on soils. High salinity increased the relative abundance of Gemmatimonadetes and Bacteroidetes and reduced the relative abundance of Actinobacteria and Acidobacteria in the Yellow River Delta . Firmicutes and Bacteroidetes were positively correlated with salinity in Xinjiang .…”
Section: Discussionmentioning
confidence: 93%